Dimensão sociotransformadora da evangelização. Constitutiva ou integrante? - Sella, Adriano (Revista Eclesiástica Brasileira, 2003)
O compromisso pela justiça, paz e transformação social se tornou, através do importante Sínodo dos Bispos de 1971 sobre “A Justiça no Mundo” e das Conferências latino-americanas dos Bispos em Medellín e Puebla, uma dimensão constitutiva da evangelização. Ou seja, a evangelização tem que assumir a dimensão sociotransformadora como essencial ou não é evangelização de Jesus Cristo. Há hoje a tendência de reduzir a evangelização novamente a uma dimensão integrante da evangelização, como se ela fosse apenas um enfeite para embelezá-la. O juízo final em Mt 25 tira qualquer dúvida: o essencial do cristianismo é a prática da justiça e do amor. Por isso, a luta pela justiça e paz é constitutiva da evangelização. Sem ela esvaziamos o Evangelho de Jesus Cristo. Abstract: Through the important Episcopal Synod held in 1971 on ‘Justice in the World’and also through the Latin American Conferences of Bishops in Medellin and Puebla, a commitment to justice, peace and social change became a constitutive dimension of evangelization. That is to say, if evangelization does not adopt a socio-transformative dimension as one of its essential features it will not be Jesus Christ’s evangelization. The tendency today is for this commitment to be considered an accessory of evangelization, a mere decoration to increase its attraction. However, in Mt. 25, the Last Judgement eliminates any doubts: the essence of Christianity is the practice of justice and of love. Thus, the struggle for justice and for peace is constitutive of evangelization. Without it we empty the Gospel of Jesus Christ.